2021
DOI: 10.1111/bjd.19812
|View full text |Cite
|
Sign up to set email alerts
|

Development or exacerbation of hidradenitis suppurativa in two transgender men after initiation of testosterone therapy

Abstract: single-nucleotide polymorphism (c.2268G>A) according to sequenced mRNA, whereas Sanger sequencing of the patient's blood detected the single-nucleotide polymorphism in a heterozygous form. The allele carrying the missense mutation is successfully transcribed into mRNA, but no protein is detected in the epidermis or keratinocytes. We assume protein degradation due to potential conformational change of the protein, resulting in protein instability and/or failure of protein-protein interaction. For now, this rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Mortimer et al discovered early on that female HS patients have an elevated testosterone and free androgen index [ 17 ]. There are three cases reported where cross-sex hormone therapy (CSHT) with testosterone resulted in an exacerbation or manifestation of HS [ 18 , 19 ]. In contrast to the above results, Harrison reports that there is no difference in testosterone between HS and healthy controls [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortimer et al discovered early on that female HS patients have an elevated testosterone and free androgen index [ 17 ]. There are three cases reported where cross-sex hormone therapy (CSHT) with testosterone resulted in an exacerbation or manifestation of HS [ 18 , 19 ]. In contrast to the above results, Harrison reports that there is no difference in testosterone between HS and healthy controls [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, this connection has not yet been proven. A subdivision between hormone-dependent and hormone-dependent HS could be interesting in the future to provide further information, as well as that cross-sex hormone therapy worsens HS, showing that androgens should be considered in HS pathogenesis [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further confirming the importance of hormones in the pathogenesis of HS, Buonomo et al observed the development or exacerbations of clinical manifestations in two transgender men following the administration of testosterone therapy [ 58 ].…”
Section: Inflammatory Skin Diseases With Alterations In Keratinocyte ...mentioning
confidence: 95%
“…Numerous studies have also associated HS with acne, hirsutism, and polycystic ovarian syndrome, supporting a role for androgens on disease ( 21 ). Furthermore, recent case reports have described new-onset and exacerbation of HS symptoms in gender dysphoric patients undergoing supplemental testosterone therapy ( 22 ). Higher proportions of androgen receptor–positive keratinocytes are found in HS lesional skin relative to healthy skin, and microarray studies indicate enrichment of androgen receptor–regulated genes in HS lesional skin ( 23 ).…”
Section: Intrinsic Immunologic Contributions To the Increased Prevale...mentioning
confidence: 99%